A review for creating a tour package: A case study for students of tourism - Solihin, Solihin; Budiarta, I Putu; Harmini, A.A.Ayu Ngurah; Susanto, Budi (Journal of Commerce, Management, and Tourism Studies, 2024)
This research aims to find out how to arrange tour packages that are competitive and can generate profits but can also satisfy consumer satisfaction, in this case, tourists. A series of activity stages are carried out before the tour package is carried out, planning, implementation, and evaluation. The planning stage includes exploring tourist destinations, creating an itinerary, and preparing human resources, logistics, and supporting supplies. The tour implementation stage includes creating a tour package and financing. The evaluation stage is the stage of reviewing the tour package by paying attention to the concepts of target market, market segmentation, and positioning. This research is qualitative research. Data from this research were obtained from observations, literature studies, and interviews with tour package organizers. The data obtained was then collected, reduced, and then analyzed.